Moral Value Analysis of Justin Bieber's Album Purpose - Manuputty, Peter; Wattimena, Juneth Nelfia; Masan, Agustinus Lia; Laurens, Jennifer (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
Language is important means of communication. Song is one of way that we can use to communicate with others. The Author or the singer uses song to communicate with their fans even want to send the message for everyone in the world. But sometimes, we as the listeners feel difficult to understand about the meaning of the song or values that contains in the song. It is moral value. Moral value is the value of behavior used by each individual to be able to interact with each other. One of Singer that uses Moral value in his song is Justin Bieber especially in his Purpose album. The purpose of this research are to analyze the kind of moral value found in Justin Bieber's songs on the album Purpose and to identify the meaning. The benefits of the research are expected to give worthy contribution for people who want to study English literature and can be reference to everyone. This research focused to find analyze 6 moral values and analyze the meaning of 10 songs on the Purpose album. The results of the research are the mostly moral value in the song lyrics of Justin Bieber's album Purpose are loyalty and sincerity, and the less moral value on this album is steadfastness